2011
DOI: 10.1038/ejcn.2011.106
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and vitamin D for obesity: a review of randomized controlled trials

Abstract: Obesity often coexists with low calcium intake and vitamin D insufficiency. There is emerging evidence of a role for these nutrients in the regulation of body weight. However, it is unclear whether increasing intakes of calcium and/or vitamin D during energy restriction, is a better strategy for weight and fat loss. We searched the literature from 2000 to date for randomized controlled trials (RCTs) on weight loss that had increased calcium or vitamin D per se, or in combination. Primary and secondary studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(73 citation statements)
references
References 67 publications
(93 reference statements)
1
63
0
9
Order By: Relevance
“…In our study, calcium intake was negatively correlated with total body fat mass and positively correlated with appendicular skeletal mass. Previous studies have shown the significant role of serum 25(OH)D status and calcium intake in fat and muscle mass [21][22][23]. Recently, Kim et al reported an inverse association between serum 25(OH)D levels and sarcopenia.…”
Section: Discussionmentioning
confidence: 95%
“…In our study, calcium intake was negatively correlated with total body fat mass and positively correlated with appendicular skeletal mass. Previous studies have shown the significant role of serum 25(OH)D status and calcium intake in fat and muscle mass [21][22][23]. Recently, Kim et al reported an inverse association between serum 25(OH)D levels and sarcopenia.…”
Section: Discussionmentioning
confidence: 95%
“…Many of these studies give cholecalciferol with or without calcium and show equivocal results. Furthermore, when calcium is given with cholecalciferol, the effects of the vitamin per se cannot be distinguished and the evidence from interventions where cholecalciferol is given alone is limited (51) . Overall, the data does not consistently support the role of vitamin D (with or without calcium) in weight or FM loss.…”
Section: Prospective and Intervention Studiesmentioning
confidence: 99%
“…cells of the adipose tissue), which suggests that vitamin D does in fact play a role in modulating this active metabolic tissue (48,49) . Evidence suggests that 1,25(OH)D plays a central role in adipocyte metabolism via the inhibition of adipogenesis, independently of parathyroid hormone concentrations (50,51) ; with lower vitamin D stores potentially increasing the differentiation of pre-adipocytes to adipocytes (i.e. adipocyte growth) (51,52) .…”
Section: Prospective and Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such recommendations serve as a basis for regulating national and/or regional nutrition policies, which considers average intake. However, no standard approach exists for deriving micronutrient recommendations (Sheffer and Lewis-Taylor 2008) (Ashwell et al 2008;Pijls et al 2009;Matthys et al 2010Matthys et al , 2011Van't Veer et al 2013).…”
Section: Nutritional Phenotype and The Complexity Of Defining Healthmentioning
confidence: 99%